1997
DOI: 10.2514/3.13569
|View full text |Cite
|
Sign up to set email alerts
|

Transient analysis of crack in composite layered medium subjected to dynamic loadings

Abstract: A semi-in® nite crack in a layered medium subjected to antiplane dynamic loading is investigated. In analyzing this problem, the fact that the re¯ections and diffractions of stress waves by the interface boundary and by the crack will generate an in® nite number of waves must be taken into account. A useful fundamental solution is proposed, and the solution is determined by superposition of the fundamental solution in the Laplace transform domain. The proposed fundamental problem is the application of exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Then it will approach its corresponding static value after the first nine waves have passed through the crack tip. Moreover, it is also found that the stress intensity factor decreases as the value of β (1) increases for this single-strip problem. The reason is that the width of the strip after linear coordinate transformation will be widened with the increment of β (1) .…”
Section: Numerical Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Then it will approach its corresponding static value after the first nine waves have passed through the crack tip. Moreover, it is also found that the stress intensity factor decreases as the value of β (1) increases for this single-strip problem. The reason is that the width of the strip after linear coordinate transformation will be widened with the increment of β (1) .…”
Section: Numerical Resultsmentioning
confidence: 87%
“…Figure 3 shows dynamic stress intensity factors of a single strip for different values of β (1) . It can be seen that the transient response jumps first from zero to a constant value, which corresponds to the appropriate static stress intensity factor of a cracked anisotropic infinite plane as indicated in Eq.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations